Evaluation and Improvement of Palliative Care: a health technology to improve the quality of death and reduce hospital oncology expenses - Melo, Cynthia de Freitas; Melo Neto, Alayson Ferreira de; Castilho, Maria Clara Cavalcante; Araújo, Danielle Feitosa (Psicooncología, 2025)
Objectives: Palliative care is an approach that promotes the quality of life of patients and their families facing any life-threatening illness, regardless of diagnosis. To this end, it requires early identification, through assessment of status, performance and decision-making. In order to facilitate this process, this research aimed to develop a mobile mHealth application designed to assess prognosis and life expectancy, support decision-making about the transition to palliative care, and offer educational content on the subject.Method: A research project was conducted to develop a scientific and technological production. Through a multidisciplinary team, with periodic meetings, integrative literature reviews on the topic were initially carried out, as well as benchmarking to identify needs and establish the requirements for the design and redesign stages of the application interface.Results: An application was created that allows patient registration, completion of performance status assessment scales, monitoring of patient history, and obtaining information via a fixed platform and through interaction with a chatbot.Conclusions: The importance of a mobile application with features that are easy to use for healthcare professionals is considered, facilitating the effective monitoring of patient progress. This tool can contribute as an addition to the therapeutic process, being used by any professional category, assisting them in making decisions about the appropriate therapeutic approach for each patient in oncology.
Keywords: Palliative Care; Status performance; Health Technology; mHealth; oncology